2022
DOI: 10.1097/md.0000000000031608
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice of umbilical cord care among young mothers of neonates in Tabora region: Analytical cross-sectional study

Abstract: Knowledge of cord care influences the choice of cord care practices and has a great impact on neonate health. Poor cord care can lead to infection of the umbilical cord and thus have a bearing on the subsequent growth trajectory of the newborn. A health facility-based analytical cross-sectional study was carried out from January-March 2021 among 315 randomly selected young mothers aged 15 to 25 years with neonates aged between 7 and 28 days. An interviewer-administered structured questionnaire was used to coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 12 publications
4
6
2
Order By: Relevance
“…The same result was found by Kalufya et al [12], (2022) about practice on umbilical cord care, 87.3% reported cleaning the umbilical cord but only 13.0% cleaned once daily as recommended. Less than half (48.9%) washed their hands with water and soap before and after cleaning of the umbilical cord, The overall practice score showed that only 66 (21%) had good cord care practice.…”
Section: Also a Study Done Entitled 'Knowledge And Practices Of Postn...supporting
confidence: 85%
See 2 more Smart Citations
“…The same result was found by Kalufya et al [12], (2022) about practice on umbilical cord care, 87.3% reported cleaning the umbilical cord but only 13.0% cleaned once daily as recommended. Less than half (48.9%) washed their hands with water and soap before and after cleaning of the umbilical cord, The overall practice score showed that only 66 (21%) had good cord care practice.…”
Section: Also a Study Done Entitled 'Knowledge And Practices Of Postn...supporting
confidence: 85%
“…Furthermore, Ndomondo et al [11], (2022) done a study in Morogoro, Tanzania, they found that 52.6% of mothers had adequate knowledge about cord care. In Tabora region/Tanzania another study done on cord care by Kalufya et al [12], (2022) they reported that more than half of young mothers 196 (62.2%) had adequate knowledge of cord care, and in Nigeria a study showed that 83.3% of mothers had awareness of umbilical cord care [13]. Also, a study found that more than half of the mothers were more aware about cord care [14].…”
Section: Also a Study Done Entitled 'Knowledge And Practices Of Postn...mentioning
confidence: 98%
See 1 more Smart Citation
“…Although the study revealed that more than half of the mothers applied medically recommended practice that is dry care method. This is greater number than studies done by Nuru in Tabora Region 14 where practice of umbilical cord care was exceptionally poor, as only 21% of them had good cord care practice, and another finding by O’Brien practiced dry cord care (n = 17, 14.9%). 15 …”
Section: Discussionmentioning
confidence: 61%
“…18 Similarly, a study conducted in Tanzania reported the association of cord care practices with the level of education, occupation, and parity. 19 The level of education is likely to influence a woman's choice of cord care practice due to the knowledge they acquire in comparison to those with low levels of education who may rely on existing cultural beliefs. Multi-parous women have experience regarding cord care and therefore first-time mothers may require proper guidance and information to avoid them tapping in to existing myths and misconceptions.…”
Section: Discussionmentioning
confidence: 99%